Volcanic sand in asphalt concrete. - Pagbilao, Dominador S.
Volcanic sand from three river sources, Abacan, Bacolor and Lubao, were investigated as an agregate component of hot mix asphalt. Laboratory test samples of asphalt mixtures containing these materials were evaluated according to their Marshall properties and their sensitivity to moisture damage. The Marshall properties of mixtures containing volcanic sand as fine aggregate were found to be inadequate. The use of volcanic sand as a partial substitute to fine aggregate, on the other hand, do not adversely affect the Marshall properties of the mixtures significantly, however, their resistance to moisture damage were significantly reduced and the binder requirement were increased by 20 percent.